OPTIMALISASI KESEHATAN SAPI POTONG MELALUI PROGRAM PENYULUHAN DAN PENGOBATAN CACING UNTUK MENINGKATKAN PRODUKTIVITAS PETERNAKAN DI KECAMATAN PAUH KOTA PADANG - Ferry Lismanto Syaiful; Khasrad Khasrad; Yulia Yellita; Mangku Mundana; Sumedi Sumedi (Jurnal Hilirisasi IPTEKS, 2024)
Livestock health is a crucial aspect of farm management efforts. Managing livestock health should be a primary concern in order to reduce the risks of losses experienced by farmers due to animal diseases. Furthermore, managing livestock health can improve welfare, productivity, resource efficiency, and the sustainability of farming operations. This activity aims to provide knowledge about the health and management of beef cattle, as well as health services helpful in mitigating the impacts of animal diseases. This activity is carried out in the Rindang Alam area, Koto Lua Village, Pauh District, Padang City. The target audience is the Mak Uniang livestock group. This activity involves lecturers, technicians, and students from the Faculty of Animal Husbandry, Andalas University. The method used is Participatory Rural Appraisal (PRA), where partnering lecturers directly act as facilitators and can facilitate the community/partners in implementing activities. The participatory learning method is used to achieve the activity targets. The implementation producers of the activity use several PRA application techniques, including education, demonstration, and activity evaluation. The activity results show an increase in farmers' understanding of livestock health management, with a value reaching 90% (perfect). Meanwhile, the training activities conducted include providing vitamins, deworming drugs, and butoxy spraying. This activity has received a high response from the community and has even improved farmers' understanding. From this activity, it can be concluded that managing livestock health should be a primary concern to reduce the risks of losses experienced by farmers due to animal diseases. Furthermore, managing livestock health can improve welfare, productivity, resource efficiency, and the sustainability of farming operations.